2020
DOI: 10.1108/jiabr-09-2016-0106
|View full text |Cite
|
Sign up to set email alerts
|

Competency model for Shari’ah auditors in Islamic banks

Abstract: Purpose The purpose of this study is to identify the competencies required of Shari’ah auditor (SAR) in the Islamic banking environment. Design/methodology/approach A qualitative approach using a multiple-case study through the semi-structured interview was used. Data was gathered from a representative of Central Bank of Malaysia, and 30 other respondents consist of the Head of Shari’ah audit (HSA) and SAR from four types of banking institutions. A focus group discussion was later conducted to validate the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…The empirical literature on this context has addressed several aspects, such as the SA association with Sukuk (Ahmed et al , 2019); professionalizing SA (Najeeb and Ibrahim, 2014); competency in Shariah auditing (Ali and Kasim, 2019; Mohd Ali et al , 2020); responsibilities of Shariah auditor (Yasoa et al , 2020b); Shariah auditor characteristics (Mohd Ali et al , 2018); challenges in Shariah practices (Puad et al , 2020); assess the implementation of the internal Shariah governance framework in selected Islamic banks (Aziz et al , 2019); the effectiveness of internal SA function (Ab Ghani et al , 2019; Shafii et al , 2013); external SA (Shafii and Salleh, 2010); SA labor market (Shafii et al , 2014a); students’ awareness of SA (Khalid et al , 2019); and Islamic legal maxims and SA practices (Abd Rahman et al , 2020). It has been reported that Shariah auditors play their roles as the third line of defense by giving assurance to the shareholders and stakeholders that all businesses and operations comply with Shariah precepts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The empirical literature on this context has addressed several aspects, such as the SA association with Sukuk (Ahmed et al , 2019); professionalizing SA (Najeeb and Ibrahim, 2014); competency in Shariah auditing (Ali and Kasim, 2019; Mohd Ali et al , 2020); responsibilities of Shariah auditor (Yasoa et al , 2020b); Shariah auditor characteristics (Mohd Ali et al , 2018); challenges in Shariah practices (Puad et al , 2020); assess the implementation of the internal Shariah governance framework in selected Islamic banks (Aziz et al , 2019); the effectiveness of internal SA function (Ab Ghani et al , 2019; Shafii et al , 2013); external SA (Shafii and Salleh, 2010); SA labor market (Shafii et al , 2014a); students’ awareness of SA (Khalid et al , 2019); and Islamic legal maxims and SA practices (Abd Rahman et al , 2020). It has been reported that Shariah auditors play their roles as the third line of defense by giving assurance to the shareholders and stakeholders that all businesses and operations comply with Shariah precepts.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 3, the investigation showed that the empirical quantitative approach was the most applied methodology in the sample studies with 19 articles (Ab Ghani and Abdul Rahman, 2015; Ahmed and Sarea, 2019), while the studies that used the qualitative approach were less with 14 studies (Alam et al , 2020; Khalid et al , 2018b). Thesis studies have discussed a variety of topics such as external SA and review committee (Alam et al , 2020), competency of SA (Mohd Ali et al , 2020) and role of Shariah auditor (Yasoa et al , 2020b), to mention some. The qualitative approach helps to understand how and why things occur.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The different positions may influence the level of knowledge that must be possessed. For example, knowledge of auditing, fiqh muamalah and Islamic banking is important knowledge for auditors in Islamic banks (Mohd Ali et al, 2020).…”
Section: Analysis and Discussionmentioning
confidence: 99%